Investigating the structure-function relationships of Plasmodium Haem Detoxification Protein and Phosphatidylinositol 4-kinase - Wambua, Lynn (Department of Chemistry, 2023)
The human malaria parasite Plasmodium falciparum relies on proteins and protein-mediated processes to survive, replicate in the host and evade the host's immune response. This study focuses on two Plasmodium proteins: (i) Haem Detoxification Protein (HDP) which has been reported to catalyse haemozoin formation in Plasmodium and (ii) Phosphatidylinositol-4- Kinase β (PI4Kβ) which plays an essential role in multiple stages of the parasite lifecycle and is a clinically validated drug target for malaria chemotherapy. Previous efforts to characterise HDP have been limited to experiments using the refolded form of recombinant protein and the role of HDP in haemozoin formation is still unclear. The aim of this research project was to optimise expression and purification of soluble Plasmodium falciparum HDP and characterise the protein's role in haemozoin formation Efforts to optimise soluble HDP expression were effective albeit exhaustive efforts to purify HDP from the soluble fraction were unsuccessful. Purification of HDP under denaturing conditions was achieved using previously reported methods. Refolded HDP was evaluated for β-hematin formation activity, but the results indicated β-hematin formation was mediated by sodium dodecyl sulfate used in the assay rather than by HDP. HDP was co-crystalised in the presence of haem but crystals diffracted poorly. Evaluation of the predicted HDP structure based on homology modelling showed that the four histidine residues predicted to facilitate haemozoin formation are not aligned in a way that would facilitate haemozoin crystal growth. This, coupled with the data from the biochemical assays, suggests HDP is unlikely to be involved in haemozoin formation. The second aim of this project was to use Plasmodium vivax PI4Kβ inhibition assays coupled with site-directed mutagenesis and mass spectrometry to support target-based malaria drug discovery programs focused on the development of both ATP-competitive and covalent Plasmodium PI4Kβ inhibitors. Two residues of interest in Plasmodium vivax PI4Kβ unique to Plasmodium, F832 and C1327, were mutated to alanine. F832 is thought to form key Pi-Pi interactions with inhibitors and C1327, found on the periphery of the catalytic site, is a potential target for covalent inhibitors. Site-directed mutagenesis was used to introduce mutations at F832 and C1327 in wild-type Plasmodium vivax PI4Kβ and wild-type PI4Kβ and the two mutants were expressed and purified. Kinetic characterisation revealed the three enzymes had similar kinetic parameters. Inhibition data indicated the F832 mutation to alanine had a minimal effect on inhibition of PI4Kβ. A time-dependent inhibition assay was established to evaluate targeted covalent inhibitors (TCIs) using wild-type PI4Kβ and the PI4Kβ C1327A mutant. A distinct decrease in wild-type PI4Kβ IC50 was observed with increasing enzyme-inhibitor pre-incubation time for inhibitors containing chloroacetamide and acrylamide warheads. In contrast, PI4Kβ C1327A IC50 values were independent of enzyme-inhibitor pre-incubation time supporting C1327- mediated covalent inhibition. Mass spectrometry was used to confirm covalent modification of the targeted cysteine residue and to assess the rate of covalent bond formation. These assays provide valuable insights, which can be used to guide the optimisation of PI4Kβ inhibitors and the choice of warheads for TCIs.